(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Four hundred and twenty cattle belonging to different breed and age groups were investigated for infestation by ticks during the period from October 2018 to September 2019 in Basrah governorate, Iraq . Investigated cattle were found to be infested by four species of hard ticks namely (Hyalomma anatolicum anatolicum, Hyalomma marginatum turanicum Rhipicephalus (Boophilus) annulatus, Rhipicephalu sturanicus) .No significant difference in infestation rate was observed according to the method of cattle raising (X²=0.455, p=0.500),however, seasonal variation in infestation with significant difference was found , higher infestation rate reported in June ( 63.3%) and the lowest was in January (20%) (X² =76.740 ,p = 0.05). In the meantime blood smears samples from the same cattle were also examined by microscopy for hemoprotozoan pathogens .The examination revealed that those cattle are infected by Babesia spp. (27.14%) and Theileria spp.(19.52%). No, significant difference in infection rate was found between male and females, but a significant variation was seen among age groups, however, age group 1-3 years revealed a high rate of infection .Seasonal variation in the infection rates were observed in infected cattle. Higher infection rates of Babesiosis and Theileriosis reported in June (50%) and (36.7%) respectively.